Association of total and neutralizing SARS-CoV-2 spike -receptor binding domain antibodies with epidemiological and clinical characteristics after immunization with the 1st and 2nd doses of the BNT162b2 vaccine. Issue 40 (24th September 2021) - Michos, Athanasios; Tatsi, Elizabeth-Barbara; Filippatos, Filippos; Dellis, Charilaos; Koukou, Dimitra; Efthymiou, Vasiliki; Kastrinelli, Evangelia; Mantzou, Aimilia; Syriopoulou, Vasiliki
Abstract: Background: Data regarding the association of antibody levels elicited after immunization with the BNT162b2 mRNA COVID-19 vaccine with epidemiological and clinical parameters are limited. Methods: We prospectively measured the total (TAbs-RBD) and the neutralizing antibodies (NAbs-RBD) against the receptor binding domain (RBD) of SARS-CoV-2 spike protein in a cohort of 268 Healthcare workers before immunization, 20 days after the 1 st dose and 30 days after the 2 nd dose of the BNT162b2 vaccine. A statistical analysis for possible association of antibodies' levels with epidemiological and clinical parameters was performed. Results: The mean age (±SD) of the participants was 45.45 years (±11.93) (range: 24–70 years) and 211 (79.9%) were females. Statistically significant differences were detected regarding both TAbs-RBD and NAbs-RBD between the first and second doses of the vaccine ( P < 0.001). The median (IQR) percentage (%) of NAbs-RBD after the 1 st dose was 51.07% (31.60%) and after the 2 nd dose 95.31% (3.70%) ( P < 0.001). The correlation between the TAbs-RBD and NAbs-RBD was after the 1 st dose, Spearman's, rho: 0.861 ( P < 0.001) and after the 2 nd dose rho: 0.989 ( P < 0.001). Twenty days after the 1 st dose, 56/264 (21.2%) of the participants had low levels of NAbs-RBD, while one month after the 2 nd dose all of them had protective levels of NAbs-RBD. After the 2 nd vaccine dose, a statistically significant negative association of TAbs-RBD was detected for age ( P < 0.001), smoking ( P = 0.011), and immunosuppressive medications ( P < 0.001), while a positive association was detected for BMI ( P = 0.004) and systemic adverse events after immunization ( P = 0.001). Conclusion: A significant correlation of TAbs-RBD and NAbs-RBD was detected after both vaccine doses. Older age, smoking, and immunosuppressive medications negatively affected the final antibody level after SARS-CoV-2 immunization. Our findings emphasize the significance of the 2 nd vaccine dose especially in the older age groups.